Perkembangan Madrasah Ibtidaiyah Swasta At-Taqwa Sambas Tahun 2011-2023 di Kabupaten Sambas - Oktavia, Amalia; Posha, Beti Yanuri (Faidatuna, 2023)
In the current era, education is considered the main driving force to meet the needs of an increasingly globalized world, both in the field of improving the quality of information and in the field of improving morals and ethics, which focuses on education. This research aims to determine the history of the formation of the At-Taqwa Sambas Private Madrasah Ibtidaiyah as well as the factors that support and hinder the development of the At-Taqwa Sambas Private Ibtidaiyah Madrasah. The research method used is historical research methods including heuristics, verification, interpretation and historiography. The research results show that the history of the At-Taqwa Private Madrasah Ibtidaiyah was founded in 2011 and was founded by the leadership of the Islamic Education Foundation through the encouragement of community leaders who understand education for the younger generation. Mr. Aminuddin Hardigaluh as the driving force and other founding figures continues to invite children to study religious education at the At-Taqwa Sambas Private Madrasah Ibtidaiyah. Starting from a student population of only 11 people and 3 teachers, this has not dampened the children's enthusiasm for studying at the madrasa. As time went by, the At-Taqwa Sambas Private Madrasah also experienced many developments, including increasing the number of students, increasing facilities and infrastructure as well as more disciplined learning practices.